2003
DOI: 10.1097/01.alc.0000057940.57330.70
|View full text |Cite
|
Sign up to set email alerts
|

ADH Genotype Does Not Modify the Effects of Alcohol on High‐Density Lipoprotein

Abstract: The concept that alcohol dehydrogenase genotype and alcohol metabolic rate modify the effects of alcohol on plasma HDL concentration is not supported by our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…This has been confirmed in other populations [43], [44]. In addition an interaction between ADH1c and the level of alcohol consumption in relation to HDL has been reported in several studies [42], [45] although not in all [43], [46].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This has been confirmed in other populations [43], [44]. In addition an interaction between ADH1c and the level of alcohol consumption in relation to HDL has been reported in several studies [42], [45] although not in all [43], [46].…”
Section: Discussionsupporting
confidence: 68%
“…The ADH1b rs1229984 GG slow genotype has been associated with elevated blood pressure, triglycerides, and uric acid in one study of Japanese [47], whereas another study on Europeans found no relation to HDL [46]. We observed a decreased fasting serum LDL level among heavy drinkers with the intermediate/fast ADH1b (rs1229984) GA/AA genotype.…”
Section: Discussionmentioning
confidence: 40%
“…Because this variant ostensibly leads to greater exposure to ethanol upon ingestion (although this has been difficult to measure), it might be anticipated to augment the effects of ethanol. Although data are not entirely consistent [193][194][195][196][197], very suggestive results from the Nurses' Health and Physicians' Health Studies suggest that the effect of alcohol on HDLC may be amplified in a dose-dependent manner among those with slow alleles [198,199]. Surprisingly, the opposite may be true for the relationships of alcohol consumption with diabetes and body weight.…”
Section: Genetic Modification Of the Alcohol-mets Relationshipmentioning
confidence: 98%
“…Other examples for genes with rare variants having an important influence on HDLC levels are the angiopoietin-like 4 (ANGPTL4) gene (variant E40K, MAF=2%) which was associated with significantly higher levels of HDLC (p=4.0×10 -7 ) in 8726 individuals of the ARIC Study (Romeo et al, 2007) or rare variants in the alcohol dehydrogenase 2 (ADH2) gene (MAF=2.8%) (Whitfield et al, 2003) or in the cytochrome P450, family 3, subfamily A, polypeptide 4 (CYP3A4) gene (MAF=0.5%) (Yamada et al, 2007) which showed significant associations in 901 and 3787 individuals, respectively.…”
Section: Common Versus Rare Variantsmentioning
confidence: 99%